Nurse-Led Multidimensional Intervention Improves Symptom Burden and Quality of Life in Hemodialysis Patients: A Quasi-Experimental Study - Fauzi, Achmad; Nurjana, Nurjana; Pardiansyah, Rustam; Hartini, Aan Nurhayati; Saptohari, Winta; Novayanti, Siska; Ningsih, Ira Kurnia (Journal of Applied Nursing and Health, 2026)
Background: Patients undergoing hemodialysis (HD) experience a high symptom burden that adversely affects health-related quality of life (HRQoL). Evidence on integrated nursing interventions to address these challenges remains limited, particularly in lower- and middle-income country (LMIC) settings. This study evaluated the effectiveness of a 12-week Multidimensional Integrated Nursing Intervention (MINI) in reducing symptom burden and improving HRQoL among HD patients in Indonesia. Methods: A multi-site quasi-experimental study with a non-equivalent pre-test/post-test control group design was conducted between November 2025 and March 2026 across three public hospitals in Indonesia. A total of 112 maintenance hemodialysis patients were allocated to either a 12-week Multidimensional Integrated Nursing Intervention (MINI; n=56) or a control group receiving usual care (n=56). The intervention integrated symptom management, psychosocial support, dietary coaching, intradialytic exercise, and self-management education. Symptom burden and health-related quality of life (HRQoL) were assessed using the MSAS-GDI and KDQOL-36, respectively, and analyzed using paired and independent t-tests, with effect sizes estimated by Cohen’s d. Results: Following 12 weeks, the MINI group demonstrated significantly greater reductions in MSAS-GDI compared to controls (1.59±0.33 vs 2.33±0.41; p<0.001; Cohen’s d=1.87). Significant improvements were observed across all five KDQOL-36 domains in the MINI group (all p<0.001; Cohen’s d=1.94), with no significant changes in the control group. Large, consistent effect sizes were observed across all three study sites. Conclusion: A 12-week nurse-led multidimensional intervention demonstrated promising reductions in symptom burden and improvements in HRQoL in HD patients across Indonesian public hospital settings. These findings suggest that MINI may be a feasible model for integration into HD nursing protocols in LMIC contexts. Confirmation through cluster-randomised or pragmatic multicenter trials with longer follow-up is warranted before routine implementation can be recommended.